2003
DOI: 10.1002/ijc.11592
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic alterations of the blood group ABO gene in oral squamous cell carcinoma

Abstract: Loss of histo-blood group A and B antigen expression is a frequent event in oral carcinomas and is associated with decreased activity of glycosyltransferases encoded by the ABO gene. We examined 30 oral squamous cell carcinomas for expression of A and B antigens and glycosyltransferases. We also examined DNA from these tumors for loss of heterozygosity (LOH) at markers surrounding the ABO locus at chromosome 9q34, for loss of specific ABO alleles, and for hypermethylation of the ABO promoters. Loss of A or B a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 41 publications
5
70
0
Order By: Relevance
“…Loss of the A or B allele was found in 3/20 tumors (15%) heterozygous for the ABO locus and hypermethylation of the promoter region in 10 of 30 tumors (33.3%). 22 Furthermore, Habuchi et al 23 reported that the region 9q32-9q33, which is in the vicinity of the ABO gene locus at 9q34.1, is a frequent target of LOH and methylation in bladder cancer. These findings prompted us to hypothesize that deletion of blood-group A antigen expression in TCC of the bladder might be regulated by a combination of genetic and epigenetic mechanisms, that is, an LOH of the ABO gene locus and hypermethylation of the ABO gene promoter region.…”
mentioning
confidence: 99%
“…Loss of the A or B allele was found in 3/20 tumors (15%) heterozygous for the ABO locus and hypermethylation of the promoter region in 10 of 30 tumors (33.3%). 22 Furthermore, Habuchi et al 23 reported that the region 9q32-9q33, which is in the vicinity of the ABO gene locus at 9q34.1, is a frequent target of LOH and methylation in bladder cancer. These findings prompted us to hypothesize that deletion of blood-group A antigen expression in TCC of the bladder might be regulated by a combination of genetic and epigenetic mechanisms, that is, an LOH of the ABO gene locus and hypermethylation of the ABO gene promoter region.…”
mentioning
confidence: 99%
“…Both Ca9-22 and OEC-M1 are gingival carcinoma and significant in the Asian population. According to the literature, besides erythrocytes, blood group antigen A, B, and H can be expressed in epithelial cells of many tissues including oral tissue, and their expression can be varied among degrees of differentiation, but decreased in tumor tissue of OSCC (41,42). The loss of blood group antigens in OSCC specimens correlates significantly with both the stage and histological grade of malignancy (42).…”
Section: Discussionmentioning
confidence: 99%
“…Links between ABO blood groups with benign or malignant diseases, such as gastric and pancreas cancers, have been observed for a long time (Wang et al, 2012;Wolpin et al, 2009). It was proved that ABO blood group antigen expression on cancer cells was modified by hypermethylation of ABO gene promoter (Gao et al, 2004), which might be related with the invasiveness or metastasis of tumor. A latest research suggested that blood type A or AB was associated with an increased risk of NPC compared with subjects with blood type O (Sheng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%